Fracture Resistance of Premolars Restored by Various Types and Placement Techniques of Resin Composites - Horieh Moosavi; Mahsa Zeynali; Zahra Hosseini Pour (Hindawi Limited, 2012)
To verify the fracture resistance of premolars with mesioocclusodistal preparations restored by different resin composites and placement techniques. Sixty premolars were randomly divided into two groups based on type of composite resin: Filtek P60 or Nulite F, and then each group was separated into three subgroups: bulk, centripetal, and fiber insert according to the type of placement method (n=10). Single-bond adhesive system was used as composite bonding according to the manufacturer's instructions. Specimens were restored in Groups 1, 2, and 3 with Filtek P60 and in Groups 4, 5, and 6 with Nulite F. After being stored 24 hours at 37∘C, a 4 mm diameter steel sphere in a universal testing machine was applied on tooth buccal and lingual cusps at a cross-head speed of 5 mm/min until fracture occurred. Groups 3 and 6 showed higher fracture resistance than Groups 1, 2, 4, and 5. Among the placement techniques, the fiber insert method had a significant effect, but the type of composite was ineffective. The insertion technique in contrast to the type of material had a significant influence on the fracture resistance of premolar teeth.